2002
DOI: 10.1023/a:1020166215457
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this article, elements of rational choice theory and integration theory are compared on the basis of their explanatory power to explain variance in academic progress. It is argued that both theoretical concepts could be combined. Furthermore the distinction between social and academic integration which integration theory makes is abandoned. Empirical tests, using AMOS (Analysis of Moment Structures), show that an extended model, comprising both integration and rational choice theory, provides the best expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…This is in line with the study of Berger and Milem (1999) but in contrast with the studies of Beekhoven et al (2002) and Eimers and Pike (1997). In these studies, majority students showed either a higher or lower levels of interaction.…”
Section: Discussion Of the Main Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…This is in line with the study of Berger and Milem (1999) but in contrast with the studies of Beekhoven et al (2002) and Eimers and Pike (1997). In these studies, majority students showed either a higher or lower levels of interaction.…”
Section: Discussion Of the Main Findingssupporting
confidence: 86%
“…In the literature, we find different definitions and operationalization of the concepts academic and social integration (Beekhoven, De Jong, & Van Hout, 2002;Berger & Milem, 1999;Braxton, Milem, & Sullivan, 2000;Cabrera, Nora, & Al, 1992;Eimers & Pike, 1997;Pascarella, Duby, & Iverson, 1983). For example, Cabrera et al (1992) measure academic integration by students' academic experience and performance and social integration by their friendship with peers.…”
Section: Student Integrationmentioning
confidence: 99%
“…In their study, integration was measured using a revised version of an integration scale developed by Pascarella and Terenzini (1980): academic integration items pertained to academic and intellectual development and social integration items pertained to interactions with peers and with faculty outside of the classroom environment. In another study, Kamphorst, Hofman, Jansen, and Terlouw (2015) measured integration using a subset of items from a scale developed by Beekhoven, De Jong, and Van Hout (2002) comparing male and female engineering students on several variables including integration. In their study, academic integration was measured using items pertaining to student satisfaction with the learning environments and faculty interactions, and social integration was measured using items pertaining to satisfaction with student interactions.…”
Section: Applications and Critiques Of Tinto's Modelmentioning
confidence: 99%
“…While Tinto's model has been widely used in educational research, it has faced criticism, especially regarding its application in diverse contexts as well as for its inconsistent use and measurement of the integration constructs (e.g., Ashar & Skenes, 1993;Bean & Metzner, 1985;Tierney, 1992;Beekhoven et al, 2002). Some of this criticism relates to Tinto's model specifically and the need for a new theoretical foundation, including critiques that (a) Tinto's model is only applicable for traditional students at residential institutions; and (b) Tinto's model lacks cultural considerations for racial and ethnic minorities.…”
Section: Applications and Critiques Of Tinto's Modelmentioning
confidence: 99%
“…Beekhoven, De Jong, & Van Hout, 2002;Van den Berg & Hofman, 2005) as registered by the university administration. More specifically, the following categories were used: "passed" (60 credits), "provisionally passed" (between 40 and 59 credits), "failed" (less than 40 credits), and "stopped" (average obtained credits in this group was 5).…”
Section: Academic Successmentioning
confidence: 99%